The Effect of Baby Massage on Sleep Quality in Toddlers at the KNDJH Orphanage, Kedungkandang District - Riries Arista Novianti; Lisna Lisna; Arys Hasta (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
One of the variables that influences a baby's development is sleep and rest. The quality of a baby's sleep is influenced by the comfort factor of the baby's body. Baby massage is one way to reduce sleep problems. Baby massage techniques are different from massage for adult humans. This community service activity aims to provide education to caregivers in orphanages about baby massage, which is linked to the quality of toddlers' sleep. The method used is outreach using media in the form of health promotion through pamphlets, complete with a pre-post test to measure the effectiveness of the exercise. The counseling went well and was easy for participants to understand. This is known from the evaluation results where there was an increase in participants' knowledge from 0% to 100% after the material was given. One of the participants stated that quite good changes in sleep quality had occurred when physiotherapy was implemented in the orphanage. These findings indicate the success of the activity. Intensive outreach is still needed to expand the positive impact of baby massage in the public.